Localización del foramen mandibular según la cantidad de los alvéolos dentales - Valente, Vitor Bonetti [UNESP]; Arita, Welton Massato [UNESP]; Gonçalves, Pedro César Garcia [UNESP]; Campos, Juliana Álvares Duarte Bonini [UNESP]; Capote, Ticiana Sidorenko de Oliveira [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The aim of this study was to analyze the anatomotopographic location of the mandibular foramen in the right and left ramus, and to verify the influence of the amount of dental alveoli on the foramen position. Thirty-five adult dry human mandibles of Araraquara Dental School, UNESP - São Paulo State University were assessed, with or without dental alveoli. Measurements were obtained, using a ruler and a digital caliper. The following distances were measured: FI - distance between the lowest point of the mandibular incisure and the mandibular foramen (F point); FB - distance between the mandibular base and F point; FP - distance between the posterior margin of the ramus and F point; FA - distance between the anterior margin of the ramus and F point; FT - distance between the apex of the retromolar trigone and F point. The Mann-Whitney test was used to compare each measurement according to hemi-arch, and the Kruskal-Wallis test was used to analyze the influence of the presence of alveoli on the measures. For multiple comparison, Dunn's method was used. There was no statistically significant difference in the location of the mandibular foramen when compared to the right and left hemi-arches. The amount of dental alveoli influenced, significantly, only on FA and FP distances. Thus, it was concluded that the right and left mandibular ramus showed symmetry in the location of the mandibular foramen, and the amount of alveoli influenced on the distances of the anterior and posterior margins of the mandibular ramus, in relation to the mandibular foramen.
Location of the mandibular foramen according to the amount of dental alveoli
Keywords: Anatomy; Mandibular anatomy; Mandibular foramen